Components design and performance analysis of a novel compressed carbon dioxide energy storage system: A pathway towards realizability. (1st February 2021) - Zhao, Pan; Xu, Wenpan; Zhang, Shiqiang; Gou, Feifei; Wang, Jiangfeng; Dai, Yiping
Abstract: To improve the penetration level of renewable energies can give strong support to the development of low-carbon society. Energy storage technologies with excellent performance are benefit to handle the associated problems arise from the fluctuation of renewables. Carbon dioxide is now recognized as a favorite working medium in compressed gas energy storage system. In order to approach the realization of a preferable carbon dioxide based energy storage system, the components design and performance analysis of a novel compressed carbon dioxide energy storage system is proposed in this paper. Firstly, the carbon dioxide compressor and all heat exchangers are designed by considering the real physical properties of carbon dioxide. Then, the system performances under design and off-design conditions are investigated according to the designed heat exchangers, compressor predicted performance maps and the models of other components. Results show that the charge time is 2.02 h, and the discharge time in constant pressure mode and variable pressure mode are 3.64 h and 2.88 h, respectively. The roundtrip efficiency in constant pressure mode is 64.96% with a stable output power, whereas the roundtrip efficiency in variable pressure mode can reach 67.37%. In constant pressure mode, the increased load level results in a raised energy density and a parabolic trend with optimal value at 65.16% in roundtrip efficiency. In variable pressure mode, the turbine inlet temperature has a positive effect on system energy density, whereas the roundtrip efficiency has a parabolic trend. Highlights: Novel layout of compressed carbon dioxide energy storage system is proposed. The actual heat transfer processes are used for all heat exchangers design. The feature of saving compression work is guided for compressor design. Comprehensive performance covered design and off-design conditions is executed.